MODIFICATION OF PERFORMANCE INDICATORS USING KANBAN METHOD AND GROWTH IN PRODUCTION LEVEL - Andrei DIMITRESCU; Ana-Maria ALECUSAN; Claudiu BABIS; Elisabeta NICULAE (BANICA); Loredana DASCALU (Fiabilitate şi Durabilitate)
The Kanban method is based on the principle of taking over the tasks by the team members as they become available (pull system), and not on the placement of the tasks without their being requested by the person to execute them (push system).Using the Kanban method, components are manufactured only when needed, so extra components are eliminated. As there is no extra production, waste cuts and scrap are reduced.